Improvement of Accessibility in Medical and Healthcare Websites - Acosta-Vargas, Gloria (2021)
Health information on the Web can make patients better informed about a disease, which according to several studies leads to better treatment results. However, the health information found on the Web is not accessible because it presents barriers that prevent people from easily accessing it because it does not comply with the standards of the Web Content Accessibility Guidelines (WCAG) 2.1. Therefore, in this study, we present an analysis of the accessibility of the seven most visited health websites in the world. To analyze the accessibility of medical websites, we apply an automatic review method. The results show that health websites have frequent problems related to the lack of alternative text, empty links, and contrast errors. This research can contribute to future work related to accessibility in health and medical sites. Finally, we suggest designing a combined method to review each website’s accessibility barriers to complement the automatic review.